Hot-rolling roll outer layer material and composite roll for hot rolling
A high-entropy alloy composition for hot rolling rolls addresses wear resistance and surface roughening issues by optimizing mixing entropy, enthalpy, and melting point, resulting in enhanced durability and product quality.
Patent Information
- Application Number
- JP2023107126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-06-29
AI Technical Summary
Conventional hot rolling rolls face issues with wear resistance and surface roughening due to the difference in hardness between carbides and their base, leading to quality defects in steel sheets.
A high-entropy alloy composition for the outer layer of hot rolling rolls is developed, utilizing a specific range of mixing entropy, enthalpy, and average melting point to create a uniform structure with minimal hardness variation, enhancing wear resistance and surface roughening resistance.
The solution provides hot rolling rolls with improved wear resistance and reduced surface roughening, ensuring consistent product quality and increased rolling efficiency by minimizing hardness differences between carbides and the base material.
Smart Images

Figure 2025006374000012 
Figure 2025006374000001 
Figure 2025006374000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an outer layer material for a rolling roll and a composite roll for rolling that are suitable for hot rolling. [Background technology]
[0002] In recent years, the demand for high-quality steel sheets has been increasing, and accordingly, there is a demand for improving the hot rolling technology of steel sheets. Therefore, there is a strong demand for improving the properties of hot rolling rolls used in hot rolling equipment and in contact with the steel sheets, particularly the wear resistance. In order to solve such problems and improve the wear resistance, high-speed steel rolls are used, which are based on high-speed steel, a type of tool steel, and contain carbide-forming elements such as V, Cr, Mo, and W, and have a large amount of hard carbides such as V-based MC-type carbides, Mo-based M2C-type carbides, and Cr-based M7C3-type carbides (M indicates a metal element that forms carbides) to improve hardness.
[0003] Conventionally, various techniques for improving the wear resistance have been disclosed. For example, Patent Document 1 discloses a technique for a rolling roll that is an Fe-based alloy containing, by mass%, C: 1.0-2.6%, Cr: 4.0-10.0%, Mo: 5.0-10.0%, W: less than 5.0%, and V: 3.0-8.0%, and satisfies 12.0%≦2Mo+W≦20.0%, 2Mo / W≧3.0, and 0.2%≦C-0.24V≦0.7%. It is said that this produces MC, M4C3, M2C, and M6C carbides that particularly contribute to wear resistance in an optimal range, and thus a rolling roll with excellent wear resistance can be obtained.
[0004] Patent Document 2 also describes the composition, in mass%, of C: 0.7-3.6%, Si: 0.2-2.5%, Mn: 0.2-2.0%, Cr: 2.0-10%, Mo: 0.2-10%, V: 2.0-10%, B: 0.001-0.50%, Al: 0.001-0.50%, Ti: 0.001-0.50%, Zr: 0.001-0.50%, Cu: 0. The technology of the outer layer material of a rolling composite roll containing 0.001-0.50% Mn, 0.001-0.50% Mg, 0.001-0.50% Ca, the balance being Fe and unavoidable impurities, and further containing one or more of Ni: 0.1-10%, W: 0.2-10%, Nb: 0.2-10%, and Co: 0.2-10% is disclosed. As a result, it is said that by obtaining a microstructure in which MC carbides are finely and uniformly crystallized in a spherical shape, it is possible to obtain an outer layer material of a rolling composite roll with excellent wear resistance.
[0005] Patent Document 3 discloses a technology of a composite roll for hot rolling, which has a chemical composition containing, on a mass basis, 1-3% C, 0.4-3% Si, 0.3-3% Mn, 1-5% Ni, 2-7% Cr, 3-8% Mo, 3-7% V, and 0.01-0.12% B, with the balance being Fe and unavoidable impurities, and satisfies the relationship represented by formula (1): Cr / (Mo+0.5W)<-2 / 3[C-0.2(V+1.19Nb)]+11 / 6 (however, when optional components W and Nb are not contained, W=0 and Nb=0), and contains, by area ratio, 1-15% MC carbide, 0.5-20% carboboride, and 0.5-20% Mo-based carbide. This makes it possible to obtain a composite roll for hot rolling with excellent wear resistance by using MC carbide.
[0006] Patent Document 4 describes a group consisting of, on a mass basis, C: 1.50 to 2.70%, Si: 0.3 to 3%, Mn: 0.1 to 3%, Ni: 0.1 to 2.5%, Cr: 4.0 to 7.0%, Mo: 4.1 to 8.0%, V: 5.0 to 10.0%, W: 0 to 0.4%, Nb: 0.1 to 3.0%, N: 0.005 to 0.15%, B: 0 to 0.05%, and further consisting of Co: 0.1 to 5%, Zr: 0.01 to 0.5%, Ti: 0.05 to 0.5%, and Al: 0.001 to 0.5%. The present invention discloses a technology for a centrifugally cast composite roll for rolling having excellent wear resistance, which comprises an Fe alloy containing at least one selected from the group consisting of Fe and inevitable impurities as the balance, and has a ratio V / Nb of the V content (mass%) to the Nb content (mass%) of 1 to 20.0, and a C-bal value of 0 to 0.28 as expressed by the following formula: C-bal=C%-0.2×V%-0.06×Cr%-0.063×Mo%-0.033×W%-0.13×Nb% [wherein C%, V%, Cr%, Mo%, W% and Nb% are the contents (mass%) of C, V, Cr, Mo, W and Nb, respectively.]. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2004-183085 A [Patent Document 2] JP 2002-161331 A [Patent Document 3] International Publication No. 2015 / 045984 [Patent Document 4] JP 2020-022989 A [Non-patent literature]
[0008] [Non-Patent Document 1] Akira Takeuchi;Materials Transactions,Vol.46,No.12(2005) Summary of the Invention [Problem to be solved by the invention]
[0009] However, as the demand for high-quality steel sheets increases and the hot rolling technology of steel sheets improves, the characteristics required for hot rolling rolls become increasingly strict, and not only wear resistance but also surface roughness resistance is strongly required. In the techniques described in Patent Documents 1 to 4, the wear resistance of hot rolling rolls is improved by optimizing the amount of carbide generation and controlling the carbide form. However, the base of the hot rolling roll material is composed of tempered martensite and bainite, and since the base has a lower hardness than the carbide, the base is more likely to wear than the carbide. When the wear of the base progresses, the base cannot support the carbide, and the carbide chips off. Therefore, unevenness occurs between the chipped and non-chipped parts, and the unevenness of the roll surface is transferred to the rolled material, causing poor quality of the steel plate product.
[0010] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide an outer layer material for a hot rolling roll which is excellent in surface roughening resistance and wear resistance. [Means for solving the problem]
[0011] In order to solve the surface roughness caused by the difference in hardness between the carbide and the matrix of the hot rolling roll, the inventors came up with the idea of forming a uniform structure with little difference in hardness near the surface of the hot rolling roll by utilizing the effect called the "cocktail effect" of high entropy alloys, which has been actively researched in recent years, and realizing high hardness. The cocktail effect utilizes the manifestation of physical properties that exceed the values predicted by the mixture rule, which are caused by nonlinear interactions between various constituent atoms.
[0012] The present inventors have investigated the relationship between chemical components (composition) and hardness in detail and found the following. That is, the chemical components are optimized so that the mixing entropy, mixing enthalpy, and average melting point calculated from the melting points of the pure elements and the composition ratio of each element are within an appropriate range. This makes it possible to manufacture a hot rolling roll outer layer material that is castable and has improved surface roughening resistance and wear resistance.
[0013] The present invention has been completed based on these findings and further investigations. That is, the gist of the present invention is as follows.
[0014] [1] Mixing entropy ΔS expressed by the following formula (1) mix is 0.0110 kJ / (mol×K) or more, and the mixing enthalpy ΔH mix is -25.0 kJ / mol or more and 5.0 kJ / mol or less, and the average melting point T m,ave A hot rolling roll outer layer material having a chemical composition that satisfies the condition of 1830K or less.
number
number
number
[0015] According to the present invention, it is possible to provide an outer layer material for a hot rolling roll which is excellent in resistance to surface roughening and wear resistance. According to the present invention, it is possible to provide a hot rolling roll outer layer material and a hot rolling composite roll which are excellent in surface roughening resistance and wear resistance and which suppress surface roughening caused by the difference in hardness between the carbide and the matrix of the hot rolling roll. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is an explanatory diagram for explaining the hot rolling wear test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The advantage of high entropy alloying is that when the constituent elements are multi-component, for example five or more components (five types), and the element contents are closer to equal composition ratios, the effect of the entropy term on the stability of the alloy when mixed in the so-called Gibbs free energy equation increases, allowing it to exist stably in a solid solution state. Also, because a crystal structure is formed from various elements with different atomic radii, latent distortion occurs in the lattice, making the matrix harder. To achieve these effects, a variety of components are added.
[0018] The outer layer material for a hot rolling roll of the present invention has a mixing entropy ΔS represented by the formula (1). mix is 0.0110 kJ / (mol×K) or more, and the mixing enthalpy ΔH mix is -25.0 kJ / mol or more and 5.0 kJ / mol or less, and the average melting point T m,ave The average melting point T m,ave is calculated from the melting points of the pure elements and their composition ratios.
[0019]
number
[0020]
number
[0021]
number
[0022] Equations (1) and (2) are based on empirical rules that are often used in high entropy alloy design. As a result of intensive research by the present inventors, the parameters ΔS mix , ΔH expressed by equation (2) mix , T represented by Eq. (3) m,ave It was found that when the above range is satisfied, a high entropy alloy with high hardness can be obtained. The T m,ave It was found that casting was possible within the above range.
[0023] ΔS mix If ΔS is less than 0.0110 kJ / (mol×K), it becomes difficult to form a high entropy alloy, and the benefits of high entropy alloying cannot be obtained. As a result, the solid solution cannot be stabilized, and the alloy is strongly affected by the contained elements, resulting in cases where sufficient hardness cannot be obtained, or where the alloy is prone to embrittlement even if it has high hardness. If sufficient hardness cannot be obtained, the wear resistance deteriorates. Also, if the alloy is prone to embrittlement even if it has high hardness, chipping of the surface occurs easily, and the resistance to roughening deteriorates. Therefore, ΔS mix must be 0.0110kJ / (mol×K) or more. ΔS mix is preferably 0.0120 kJ / (mol×K) or more, more preferably 0.0130 kJ / (mol×K) or more. mix The upper limit of is not particularly limited, but as an example, ΔS mix is less than 0.0200 kJ / (mol×K).
[0024] ΔH mix If ΔH is less than -25.0 kJ / mol or exceeds 5.0 kJ / mol, it becomes difficult to form a high entropy alloy, and the benefits of high entropy alloying cannot be obtained. As a result, the solid solution cannot be stabilized, and the alloy is strongly affected by the contained elements, resulting in cases where sufficient hardness cannot be obtained, or where the alloy is prone to embrittlement even if it has high hardness. If sufficient hardness cannot be obtained, the wear resistance deteriorates. Also, if the alloy is prone to embrittlement even if it has high hardness, chipping of the surface occurs easily, and the resistance to roughening deteriorates. Therefore, ΔH mix is between -25.0kJ / mol and 5.0kJ / mol. ΔH mix is preferably -23.0 kJ / mol or more, and more preferably -20.0 kJ / mol or more. mix is preferably 4.0 kJ / mol or less, and more preferably 2.0 kJ / mol or less.
[0025] In addition, in the present invention, ΔH ij The values of were referenced in Non-Patent Document 1.
[0026] T m,ave If the temperature exceeds 1830K, it becomes difficult to melt the material, or even if it can be melted, it cools and solidifies when poured, making it impossible to cast the material, and it becomes impossible to manufacture the outer layer material for hot rolling rolls or to evaluate its characteristics. m,ave must be 1830K or less.
[0027] In the present invention, for example, the following values are used as the melting points of the pure elements of the following elements. Al:933.15[K], Co:1768.15[K], Ni:1728.15[K], Si:1685.15[K], Ti:1939.15[K], V:2190 .15[K], Cr:2130.15[K], Fe:1809.15[K], Cu:1358.15[K], Mo:2896.15[K], W:3680.15[K]
[0028] The composition of the outer layer material of the hot rolling roll of the present invention is determined by the mixing entropy ΔS mix , the mixing enthalpy ΔH expressed by equation (2) mix and the average melting point T m,ave It is sufficient that the above range is satisfied.
[0029] A specific example of the composition includes a composition containing five or more elements, more specifically, a composition including three elements, Al, Co, and Ni, and two or more elements selected from Si, Ti, V, Cr, Fe, Cu, Mo, and W.
[0030] An example of a preferred composition includes, in atomic %, Al: more than 0% and not more than 25.0%, Co: more than 0% and not more than 35.0%, Ni: more than 0% and not more than 35.0%, and further includes two or more selected from Si: more than 0% and not more than 25.0%, Ti: more than 0% and not more than 25.0%, V: more than 0% and not more than 25.0%, Cr: more than 0% and not more than 35.0%, Fe: more than 0% and not more than 35.0%, Cu: more than 0% and not more than 45.0%, Mo: more than 0% and not more than 30.0%, and W: more than 0% and not more than 15.0%, with the balance being unavoidable impurities. The reason for this will be explained below. In the following, unless otherwise specified, atomic % will simply be written as %. Furthermore, the content means the content ratio of the element in atomic % to the entire alloy.
[0031] Al: more than 0% and less than 25.0% Al has a relatively large atomic radius compared to elements such as Fe, Co, and Ni, and is included in the crystal lattice together with these elements, which generates latent distortion in the lattice and is effective in increasing hardness. However, when the Al content exceeds 25.0%, the alloy tends to become brittle. In addition, Al that is not dissolved in the solid solution causes a decrease in hardness, and furthermore, the element distribution becomes uneven, and the variation (hardness difference) in the Vickers hardness in the outer layer material for hot rolling rolls also becomes large. Therefore, the Al content is preferably more than 0% and 25.0% or less. The Al content is more preferably 24.0% or less, and even more preferably 22.0% or less. In addition, the Al content is more preferably 0.1% or more, even more preferably 2.0% or more, and even more preferably 5.0% or more.
[0032] Co: more than 0% and less than 35.0% Co is preferably contained in the components because it increases the effect of the entropy term on the stability of the alloy and stabilizes the solid solution. However, if the Co content exceeds 35.0%, the entropy term decreases and high-entropy alloying tends to become unstable. Therefore, the Co content is preferably more than 0% and 35.0% or less. The Co content is more preferably 34.0% or less, and even more preferably 32.0% or less. The Co content is more preferably 0.1% or more, even more preferably 8.0% or more, and even more preferably 10.0% or more.
[0033] Ni: more than 0% and less than 35.0% Ni, like Co, is preferably contained in the components because it increases the effect of the entropy term on the stability of the alloy and stabilizes the solid solution. However, when the Ni content exceeds 35.0%, high entropy alloying tends to become unstable. Therefore, the Ni content is preferably more than 0% and 35.0% or less. The Ni content is more preferably 34.0% or less, and even more preferably 32.0% or less. The Ni content is more preferably 0.1% or more, even more preferably 8.0% or more, and even more preferably 10.0% or more.
[0034] In one example of a preferred composition of the present invention, in addition to the above-mentioned components, two or more selected from the following may be contained: Si: more than 0% and 25.0% or less, Ti: more than 0% and 25.0% or less, V: more than 0% and 25.0% or less, Cr: more than 0% and 35.0% or less, Fe: more than 0% and 35.0% or less, Cu: more than 0% and 45.0% or less, Mo: more than 0% and 30.0% or less, and W: more than 0% and 15.0% or less. When these elements are contained, the crystal lattice is composed of elements with different atomic radii, and potential distortion occurs in the lattice, making it easier to increase hardness and stabilizing high entropy alloying. For this reason, it is preferable to contain two or more selected from Si, Ti, V, Cr, Fe, Cu, Mo, and W within the above content range. In addition, ΔS mix , ΔH mix , T m,ave The elements contained and their contents are appropriately adjusted so that the content falls within an appropriate range.
[0035] In addition, in the case where two or more elements selected from Si, Ti, V, Cr, Fe, Cu, Mo, and W are contained, the ranges of the contents of the contained components are shown below. When Si is contained, the Si content is more than 0%, preferably 0.1% or more, more preferably 2.0% or more, and even more preferably 4.0% or more. When Si is contained, the Si content is 25.0% or less, preferably 24.0% or less, and more preferably 22.0% or less. When Ti is contained, the Ti content is more than 0%, preferably 0.1% or more, more preferably 2.0% or more, and further preferably 4.0% or more. When Ti is contained, the Ti content is 25.0% or less, preferably 24.0% or less, and more preferably 22.0% or less. When V is contained, the V content is more than 0%, preferably 0.1% or more, more preferably 2.0% or more, and further preferably 5.0% or more. When V is contained, the V content is 25.0% or less, preferably 24.0% or less, and more preferably 22.0% or less. When Cr is contained, the Cr content is more than 0%, preferably 0.1% or more, more preferably 5.0% or more, and further preferably 10.0% or more. When Cr is contained, the Cr content is 35.0% or less, preferably 32.0% or less, and more preferably 28.0% or less. When Fe is contained, the Fe content is more than 0%, preferably 0.1% or more, more preferably 2.0% or more, and even more preferably 5.0% or more. When Fe is contained, the Fe content is 35.0% or less, preferably 32.0% or less, and more preferably 30.0% or less. When Cu is contained, the Cu content is more than 0%, preferably 0.1% or more, more preferably 5.0% or more, and further preferably 10.0% or more. When Cu is contained, the Cu content is 45.0% or less, preferably 44.0% or less, and more preferably 42.0% or less. When Mo is contained, the Mo content is more than 0%, preferably 0.1% or more, more preferably 8.0% or more, and even more preferably 10.0% or more. When Mo is contained, the Mo content is 30.0% or less, preferably 28.0% or less, and more preferably 26.0% or less. When W is contained, the W content is more than 0%, preferably 0.1% or more, and more preferably 0.4% or more. When W is contained, the W content is 15.0% or less, preferably 12.0% or less, and more preferably 8.0% or less. In addition, in one example of the above-mentioned preferable component composition, two or more selected from Si, Ti, V, Cr, Fe, Cu, Mo and W may be contained, but the content of components that are not contained among these may be 0%.
[0036] Remainder: unavoidable impurities In one example of a preferred composition of the present invention, the remainder other than the above-mentioned components can be unavoidable impurities. Examples of unavoidable impurities include P, S, Mg, Zr, REM (rare earth metals), Sn, As, Sb, Bi, Pb, Zn, N, and O. However, as long as the effects of the present invention are not impaired, it is not rejected to contain P, S, Mg, Zr, and REM at 0.03% or less, Sn, As, and Sb at 0.05% or less, and Bi, Pb, Zn, N, and O at 0.01% or less. Here, REM is a general term for 17 elements in total, including Sc, Y, and lanthanoid elements. One or more of these 17 elements can be contained as unavoidable impurities, and the REM content means the total content of these elements.
[0037] In addition, in one example of the preferred component composition of the present invention described above, the total content of Al, Co, and Ni is preferably 35.0 to 82.0% in atomic %. When the total content of Al, Co, and Ni is within the above range, it becomes easier to realize high entropy alloying and to stably increase hardness. The total content of Al, Co, and Ni is more preferably 38.0% or more, and even more preferably 40.0% or more, in atomic %. The total content of Al, Co, and Ni is more preferably 80.0% or less, and even more preferably 78.0% or less, in atomic %.
[0038] The structure of the outer layer material for hot rolling roll of the present invention is not particularly limited. The structure of the outer layer material preferably has a single crystal structure. In addition, the outer layer material preferably satisfies the following ranges of average Vickers hardness and the range of difference between the maximum and minimum values of the measured Vickers hardness.
[0039] The hot rolling roll outer layer material of the present invention has the above-mentioned component composition, and the hardness of the outer layer material is preferably 620HV or more and 850HV or less in terms of average Vickers hardness measured at 20°C. When the average Vickers hardness is 620HV or more, the wear resistance is further improved. On the other hand, when the average Vickers hardness is 850HV or less, cracks formed on the surface of the hot rolling roll during hot rolling can be easily ground and removed. The average Vickers hardness is more preferably 630HV or more, and even more preferably 650HV or more. Moreover, the average Vickers hardness is more preferably 820HV or less, and even more preferably 800HV or less. The average Vickers hardness measured at 20°C is determined by measuring the Vickers hardness HV of the test material (hot rolling roll outer layer material) at 20°C using a Vickers hardness tester (test force: 50 gf) at 25 points under the following conditions: diamond indenter, air atmosphere, load holding time of 10 seconds, and calculating the average value. The Vickers hardness HV is measured at the center of the thickness of the hot rolling roll outer layer material.
[0040] In addition, the outer layer material for hot rolling rolls of the present invention preferably has a difference between the maximum and minimum Vickers hardness values measured at 20°C as described above of 120 HV or less. When the difference is 120 HV or less, it becomes easier to suppress surface roughness caused by the difference in hardness between the carbide and the matrix, which has been a problem in conventional outer layer materials for hot rolling rolls. The difference is more preferably 100 HV or less, and even more preferably 80 HV or less.
[0041] Next, a preferred method for producing the outer layer material for hot rolling roll and the composite roll for hot rolling according to the present invention will be described.
[0042] A preferred method for producing the hot rolling roll outer layer material of the present invention is to pour the molten metal having the above-mentioned composition of the hot rolling roll outer layer material into a mold and cast it. Specifically, the molten metal having the above-mentioned composition of the hot rolling roll outer layer material is poured into a rotating mold, the inner surface of which is covered with a refractory material mainly made of zircon or the like to a thickness of 1 to 5 mm, so as to have a predetermined thickness, and centrifugal casting is performed.
[0043] In one preferred embodiment of the production method of the present invention, the mixing entropy ΔS of the component composition of the molten metal is calculated by the above formula (1). mix and calculating the mixing enthalpy ΔH of the component composition by the above formula (2). mix and calculating the average melting point T m,ave Then, the calculated mixing entropy ΔS mix , mixing enthalpy ΔH mix , average melting point T m,ave After it is confirmed that the mixed entropy ΔS satisfies the predetermined range, the molten metal is poured into a mold to cast the outer layer material for a hot rolling roll. mix , mixing enthalpy ΔH mix , average melting point T m,ave If one or more of the following do not meet the specified range, the components are adjusted and the mixing entropy ΔS mix , mixing enthalpy ΔH mix , average melting point T m,ave The molten metal after the composition adjustment can be poured into a mold to cast an outer layer material for a hot rolling roll.
[0044] The hot rolling composite roll of the present invention has a centrifugally cast outer layer and inner layer when the roll outer layer material is cast by centrifugal casting. The hot rolling composite roll of the present invention may be composed of the outer layer and the inner layer welded and integrated with the outer layer. An intermediate layer may be disposed between the outer layer and the inner layer. That is, instead of the inner layer welded and integrated with the outer layer, an intermediate layer welded and integrated with the outer layer and an inner layer welded and integrated with the intermediate layer may be used. The inner layer is preferably manufactured by static casting.
[0045] For the inner layer to be statically cast, it is preferable to use spheroidal graphite cast iron, worm-shaped graphite cast iron (CV cast iron), or the like, which has excellent castability and mechanical properties. In a centrifugal cast roll, the outer layer and the inner layer are integrated by welding, and the components of the outer layer material are mixed into the inner layer. If carbide-forming elements such as Cr and V contained in the outer layer material are mixed into the inner layer, it weakens the inner layer. For this reason, it is preferable to suppress the mixing rate of the outer layer material components as much as possible.
[0046] In addition, when an intermediate layer is formed, it is preferable to use graphite steel, high carbon steel, hypoeutectic cast iron, etc. as the intermediate layer material. The intermediate layer and the outer layer are integrated by welding, and the components of the outer layer material are mixed into the intermediate layer. In order to suppress the mixing rate of the outer layer material components into the inner layer, it is preferable to suppress the mixing rate of the outer layer material into the intermediate layer as much as possible.
[0047] As a result of the above, a composite roll for hot rolling having three layers, that is, an outer layer, an intermediate layer, and an inner layer, or two layers, that is, an outer layer and an inner layer, can be obtained. EXAMPLES
[0048] The present invention will be described in more detail with reference to the following examples, but the present invention is not limited to these examples.
[0049] The steel was heated to 1450-1600°C and melted to obtain a molten metal having the composition shown in Table 1. The molten metal was then poured into a Y-shaped keel block mold (rectangular parallelepiped portion: thickness 35 mm, width 230 mm, height 120 mm) and cast to produce test materials No. 1-17 of the present invention and test materials No. 18-31 of the comparative examples. After cooling, the test materials were removed and subjected to hardness measurements and hot rolling wear tests. The test pieces used for the measurements and tests were taken from the center of the wall thickness of the test materials. Note that, m,ave Anything above 1830K could not be cast, and test materials could not be produced.
[0050] Regarding the composition of the molten metal, the mixing entropy ΔS is calculated by the above formula (1). mix , the mixing enthalpy ΔH according to the above formula (2) mix , the average melting point T m,aveThe calculated mixing entropy ΔS mix , mixing enthalpy ΔH mix , average melting point T m,ave It was confirmed whether the mixed entropy ΔS of the present invention example shown in Table 1 satisfies the predetermined range. mix , mixing enthalpy ΔH mix , average melting point T m,ave However, if the specified range is met, the molten metal having the composition is poured into the mold and casting is performed. If the specified range is not met, the composition is adjusted, and after it is confirmed that the specified range is met, the molten metal having the composition after the composition adjustment is poured into the mold and casting is performed. The composition shown in Table 1, ΔS mix , ΔH mix , T m,ave is that of the molten metal poured into the mold (i.e., the test material prepared).
[0051] Here, taking the test material No. 1 shown in Table 1 as an example of the present invention, from the component composition, ΔS mix , ΔH mix , T m,ave A method for calculating the above will now be specifically described.
[0052] First, the elements contained in test material No. 1 are seven types: Al, Co, Ni, Ti, V, Cr, and Fe. The order of the elements in formulas (1), (2), and (3) is random, but for calculation purposes, Al is placed first and Fe is placed seventh. From Table 1, x Al =0.167, x Co =0.167, x Ni = 0.167, x Ti = 0.083, x V = 0.082, x Cr = 0.167, x Fe = 0.167, and by calculating equation (1), ΔS mix = 0.0158 kJ / (mol×K).
[0053] Also, from Non-Patent Document 1, ΔH ij The values of [kJ / mol] are ΔH AlCo =-19, ΔHAlNi =-22, ΔH AlTi =-30, ΔH AlV =-16, ΔH AlCr =-10, ΔH AlFe =-11, ΔH CoNi = 0, ΔH CoTi =-28, ΔH CoV =-14, ΔH CoCr =-4, ΔH CoFe =-1, ΔH NiTi =-35, ΔH NiV =-18, ΔH NiCr =-7, ΔH NiFe =-2, ΔH TiV =-2, ΔH TiCr =-7, ΔH TiFe =-17, ΔH VCr =-2, ΔH VFe =-7, ΔH CrFe =-1 was adopted. For test material No. 1, expanding the right-hand side of equation (2) gives ΔH mix =4×{(x Al x Co ×ΔH AlCo +x Al x Ni ×ΔH AlNi +x Al x Ti ×ΔH AlTi +x Al x V ×ΔH AlV +x Al x Cr ×ΔH AlCr +x Al x Fe ×ΔH AlFe )+(x Co x Ni ×ΔH CoNi +x Co x Ti ×ΔH CoTi +x Co x V ×ΔH CoV +x Co x Cr ×ΔH CoCr +x Co x Fe ×ΔH CoFe )+(x Ni x Ti ×ΔH NiTi +xNi x V ×ΔH NiV +x Ni x Cr ×ΔH NiCr +x Ni x Fe ×ΔH NiFe )+(x Ti x V ×ΔH TiV +x Ti x Cr ×ΔH TiCr +x Ti x Fe ×ΔH TiFe )+(x V x Cr ×ΔH VCr +x V x Fe ×ΔH VFe )+(x Cr x Fe ×ΔH CrFe )}, and by substituting each, ΔH mix =-18.3 kJ / mol is obtained.
[0054] As mentioned above, the melting point of a pure element is T m,Al =933.15K, T m,Co =1768.15K, T m,Ni =1728.15K, T m,Ti =1939.15K, T m,V =2190.15K, T m,Cr =2130.15K, T m,Fe = 1809.15K, and by calculating equation (3) from these values and the mole fraction, T m,ave =1738K is obtained.
[0055] [Table 1]
[0056] For test pieces cut out from the test materials of the present invention and the comparative examples, the Vickers hardness HV at 20°C was measured at 25 points for each test piece using a micro Vickers hardness tester (test force: 50 gf), and the average value was calculated. In addition, the difference between the maximum and minimum values of the Vickers hardness measured at the 25 points was calculated. The Vickers hardness measurement was performed using a Mitutoyo HM-200 testing machine in air with a load holding time of 10 seconds. In addition, measurements were performed at 3 indentations, for a total of 25 points, 5 vertical points x 5 horizontal points.
[0057] The hot rolling wear test method was as follows. Ring-shaped test pieces were taken from test materials No. 1 to 31, and hot rolling wear test pieces (outer diameter 60 mmφ, width 10 mm, with C1 chamfer) were taken from the obtained ring-shaped test pieces of each of the invention examples and each of the comparative examples. The hot rolling wear test was performed by a two-disk sliding rolling method between the test piece and the mating piece, as shown in FIG. 1. The test piece 1 was rotated at 700 rpm while being cooled with cooling water 2, and a mating piece 4 (S45C, outer diameter 190 mmφ, width 15 mm, with C1 chamfer) heated to 800°C by a high-frequency induction heating coil 3 was applied with a load of 686 N in the load direction 7 to the rotating test piece 1, and the test piece was rolled in contact with the mating piece 4. The rotation direction 5 of the test piece 1 and the rotation direction 6 of the mating piece 4 are the rotation directions in which the tangents at the contact points between the test piece 1 and the mating piece 4 are in the same direction. The abrasion test was carried out for 450 minutes, and the mating piece was replaced every 45 minutes (31,500 rotations of the test piece) for a total of 10 times (315,000 rotations of the test piece), and the average amount of abrasion per time (per 31,500 rotations of the test piece) was calculated. In addition, the test surface of the test piece after the test was observed visually and with a digital microscope to evaluate the surface roughening resistance. The results are shown in Table 2.
[0058] [Table 2]
[0059] In Table 2, the wear amount of 0.16 g / cycle or less was judged as pass (excellent wear resistance), and the wear amount of more than 0.16 g / cycle was judged as fail. In addition, the test surface was observed with a digital microscope at a magnification of 30 times, and roughness was judged to be present when unevenness was confirmed on the test surface, and roughness was judged to be absent when unevenness was not confirmed on the test surface, and roughness was judged to be pass (excellent resistance to roughness). As is clear from Table 2, the examples of the present invention are excellent in wear resistance and roughness resistance. In the examples of the present invention, the difference between the maximum and minimum values of Vickers hardness was small, and unevenness of the test surface due to the variation in Vickers hardness was suppressed, and roughness due to the hardness difference between the carbide and the base part of the conventional hot rolling roll outer layer material was not observed.
[0060] Therefore, according to the present invention, it is possible to manufacture a roll outer layer material for a hot rolling stand and a composite roll which have excellent wear resistance and suppress surface roughness caused by the difference in hardness between the carbide and the matrix of the hot rolling roll. As a result, it is possible to obtain the effects of improving the life of the hot rolling roll and reducing time loss during interruption of rolling due to roll trouble, thereby improving the rolling efficiency of the roll for the hot rolling stand and improving the productivity of hot rolled steel sheet. [Explanation of symbols]
[0061] 1: Test piece 2: Cooling water 3: High frequency induction heating coil 4: Opposite side 5: Rotation direction of the test piece 6: Rotation direction of the other piece 7: Load direction
Claims
1. Mixing entropy ΔS represented by the following formula (1) mix is 0.0110 kJ / (mol × K) or more, and the mixing enthalpy ΔH represented by the following formula (2) mix is -25.0 kJ / mol or more and 5.0 kJ / mol or less, and the average melting point T m,ave The outer layer material for a hot rolling roll has a component composition that satisfies the condition that the temperature is 1830K or less. [0010] where R is the gas constant 8.314 x 10 -3 kJ / (mol×K), i means the i-th element when n elements contained in the composition are arranged in order, and x i is the mole fraction of the i-th element. [0025] Here, ΔH ij is the mixing enthalpy [kJ / mol] in the liquid phase of an equiatomic alloy in a binary alloy. i and j represent the i-th and j-th elements when the n elements contained in the composition are arranged in order, and x i and x j are the mole fractions of the i-th and j-th elements. [0030] Here, i means that the element is the i-th element when the n elements contained in the composition are arranged in order, and T m,i is the melting point of the pure element of the i-th element [K], and x i is the mole fraction of the i-th element.
2. The composition of the components is, in atomic percent, Al: more than 0% but not more than 25.0%, Co: more than 0% and 35.0% or less, and Ni: more than 0% and 35.0% or less; moreover, Si: more than 0% but not more than 25.0%, Ti: more than 0% and less than 25.0%, V: more than 0% and less than 25.0%, Cr: more than 0% but not more than 35.0%, Fe: more than 0% but not more than 35.0%, Cu: more than 0% and 45.0% or less, Mo: more than 0% and 30.0% or less, and W: Contains two or more selected from more than 0% and 15.0% or less; 2. The outer layer material for a hot rolling roll according to claim 1, wherein the balance consists of unavoidable impurities.
3. The hot rolling roll outer layer material according to claim 2, wherein the total content of Al, Co and Ni is 35.0 to 82.0% in atomic %.
4. The hot rolling roll outer layer material according to any one of claims 1 to 3, wherein the average Vickers hardness measured at 20 ° C. is 620 HV or more and 850 HV or less, and the difference between the maximum value and the minimum value of the Vickers hardness measured at 20 ° C. is 120 HV or less.
5. A composite roll for hot rolling having two layers, an outer layer and an inner layer, or three layers, an outer layer, an intermediate layer, and an inner layer, A composite roll for hot rolling, wherein the outer layer is made of the outer layer material for hot rolling roll according to any one of claims 1 to 3.
6. A composite roll for hot rolling having two layers, an outer layer and an inner layer, or three layers, an outer layer, an intermediate layer, and an inner layer, A composite roll for hot rolling, wherein the outer layer is made of the outer layer material for hot rolling roll according to claim 4.
Citation Information
Patent Citations
High-entropy alloy reinforced high-speed steel wear-resistant material and preparation method thereof
CN114875288A
Argon arc cladding high-entropy alloy coating and preparation method thereof
CN115976511A
Production of hearth roll for heat treatment furnace
JP1990141523A
Build-up roll
JP1991118991A
Alloy structure
JP2016023351A